Engineering substrate recognition in catalysis by cytochrome P450CAM - Bell, Stephen G; Chen, Xuehui; Xu, Feng; Rao, Zihe; Wong, Luet-Lok (Chemické listy, 2003)
We have a continuing interest in applying the current knowledge of P450cam substrate recognition to engineer the enzyme for the biotransformation of unnatural substrates with the long-term aim of applications in the synthesis of fine chemicals and bioremediation of environmental contaminants. Comparison of the structure of target substrates with camphor, the natural substrate, lead to the design of active site mutations that had greatly enhanced activity for the oxidation of chlorinated benzenes and selectivity of (+)-?-pinene oxidation. The crystal structure of the F87W/Y96F/V247L mutant with 1,3,5-trichlorobenzene and (+)-?-pinene bound revealed the enzyme substrate contacts and provided insights into the activity and selectivity patterns. The structures also provided a novel basis for further engineering of P450cam for increased activity and selectivity for the oxidation of related compounds.